2018
DOI: 10.1080/02770903.2018.1424189
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hospital admission in adult patients with asthma exacerbations: A systematic review

Abstract: Factors such as patient demographics (e.g., female sex, older age), patient vital signs/severity, and history are associated with admission following ED presentation for acute asthma. These can be employed by ED clinicians to effectively discern patients at high risk for admission and lead to more evidence-based decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
8
2
1
Order By: Relevance
“…Several studies have reported that older asthma patients utilize more healthcare, including more emergency care treatment and hospitalizations. 4,24 Even though sex was not revealed to be a risk factor for asthmarelated hospitalizations in the present study, a previous systematic review identi ed female sex as a signi cant predictor of repeated hospital visits in asthmatic children. 5 We reported that low educational attainment was a signi cant risk factor for asthma-related hospitalization, which was in line with the ndings of several previous studies.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Several studies have reported that older asthma patients utilize more healthcare, including more emergency care treatment and hospitalizations. 4,24 Even though sex was not revealed to be a risk factor for asthmarelated hospitalizations in the present study, a previous systematic review identi ed female sex as a signi cant predictor of repeated hospital visits in asthmatic children. 5 We reported that low educational attainment was a signi cant risk factor for asthma-related hospitalization, which was in line with the ndings of several previous studies.…”
Section: Discussioncontrasting
confidence: 73%
“…Research from the developed world has studied possible risk factors, such as disease severity, inadequate clinical care, poor adherence to treatment, the presence of comorbidities, familial factors, behavioral factors and environmental risk factors 4,5, and has shown that older age (> 45 years), female sex, increased disease severity, previous exacerbations requiring hospitalization, overuse of beta agonists, tobacco smoke and asthma comorbidities, such as chronic rhinitis and gastroesophageal re ux disease (GORD), are associated with hospitalizations due to exacerbated asthma. 4,6,7 However, the existing evidence from developed countries is not generalizable to Sri Lankan asthma patients due to differences in sociodemographic background, lifestyle, and healthcare provision.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma attacks severe enough to require hospital admission often indicate poor management of modifiable risk factors, including comorbidities. 7 8 Several risk factors for asthma attacks have been described separately in children and adults including female sex, 9 10 11 12 a history of previous asthma-related hospital admissions, 10 13 higher disease severity, 14 older age, 9 12 belonging to an ethnic minority group, 13 15 having a history of inhaled corticosteroid use, 15 and presence of comorbidities such as allergic rhinitis, gastro-oesophageal reflux disease and obesity. 11 16 However, risk factors contributing to asthma attacks have not been studied across paediatric and adult populations simultaneously in a large population representative sample.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that female sex,9–12 previous exacerbations requiring hospital admission, 9 11 13 increased disease severity, 9 14 older age (≥45 years),9 11 12 younger age (<18), 10 15 ethnic minorities (African-American, Black and Indian),10 13 15 history of inhaled corticosteroids (ICS) (defined as ICS use in the preceding year),15 over-use of short-acting beta agonists16 and comorbidities such as chronic rhinitis and gastro-oesophageal reflux disease (GORD)11 are associated with asthma exacerbations including those requiring hospitalisation in children and adults. Previous studies also suggest that continued care and follow-up after hospitalisation reduce future asthma-related hospitalisations 17–19…”
Section: Introductionmentioning
confidence: 99%